Analisis Kadar Boraks pada Jajanan yang Dijual di SD Yang Tersebar di Desa Lenek Daya Nusa Tenggara Barat - Yossy Ayuliansari; Lalu Junaidi Halki; Wiranda Utama; Samsul Rizal (Syntax Corporation Indonesia, 2024)
This research aims to analyze the levels of borax in snacks sold in primary schools (SD) scattered across Lenek Daya Village, West Nusa Tenggara. The sampling method was conducted using purposive sampling from all primary schools in the village, followed by qualitative analysis of borax using turmeric paper. Furthermore, samples indicated positive for containing borax were analyzed for their levels based on the alkalimetric titration method. The results showed that there were 3 samples indicated positive for containing borax, namely sample A1 with a borax level of 819.8 ppm; B1 at 1175 ppm, and sample D1 at 1360.2 ppm. These findings indicate the potential existence of food safety issues among primary school children in Lenek Daya Village. Therefore, steps to enhance supervision and control of food quality in the school environment need to be increased to ensure the safety of children's snack consumption.